Condom use by Nepalese youth at last sex with most recent partner other than wife or non-live-in partner - Shakya, Dhanendra Veer (Nepal Population Journal, 2018)
This study attempts to examine the effects of some selected socio-economic variables like level of education, occupation, current working status, wealth index, place of residence and frequency of exposure to mass media like newspapers/magazines, radio and television; demographic variables like age group, age at first sex, marital status, migration status and travelling away from home in the past 12 months; and cultural variables like religion and caste/ethnicity, and spatial distribution by ecological zones, development regions and provinces on condom use by Nepalese youth males at last sex with most recent partner other than wife or non-live-in partner using multivariate logistic regression analysis. It has used 2016 Nepal Demographic and Health Survey data files with weighted cases. Data are analyzed using percentage and frequency tables and statistical tests are carried out using binomial logistic regression analysis of dependent variable controlling for the independent variables presented in the table of this study. The significant findings of the study are that youth males with primary level of education are less likely to use condom at last sex with most recent partner other than wife or non-live- in partner than those who have higher than secondary level of education. Not working youth males are more likely to use condom than those engaged agricultural occupation. Likewise, ever married youth males are less likely to use condom than their never married counterparts. Newar youth males are less likely to use condom than youth males of Hill Chhetri. Youth males living in Terai are less likely to use condom than youth males living in Hill. Similarly, youth males living in Far-western region are more likely to use condom compared to their counterparts of Central regions.